What's the Point of Spiritual Care? A Narrative Response. (June 2019) - Lasair, Simon
This article assumes spiritual care is relevant for all people, regardless of their faith affiliation. Building on the author's work in narrative spirituality, the discussion demonstrates how spiritual care practitioners can engage clients in their lived narratives, with Narrative Empowerment being the end goal. Several therapeutic practices are thus revealed, as well as three traits by which a client's Narrative Empowerment can be described and assessed.